Development of Biomimetic Hepatic Lobule-Like Constructs on Silk-Collagen Composite Scaffolds for Liver Tissue Engineering - Guo, Lina; Zhu, Ziqing; Gao, Chuanzhou; Chen, Kaiwen; Lu, Shenzhou; Yan, Hexin; Liu, Wenming; Wang, Mingqi; Ding, Yanfang; Huang, Lin; Wang, Xiuli (Frontiers in Bioengineering and Biotechnology, 2022)
Constructing an engineered hepatic lobule-mimetic model is challenging owing to complicated lobular architecture and crucial hepatic functionality. Our previous study has demonstrated the feasibility of using silk fibroin (SF) scaffolds as functional templates for engineering hepatic lobule-like constructs. But the unsatisfactory chemical and physical performances of the SF-only scaffold and the inherent defect in the functional activity of the carcinoma-derived seeding cells remain to be addressed to satisfy the downstream application demand. In this study, SF-collagen I (SFC) composite scaffolds with improved physical and chemical properties were fabricated, and their utilization for bioengineering a more hepatic lobule-like construct was explored using the immortalized human hepatocyte-derived liver progenitor-like cells (iHepLPCs) and endothelial cells incorporated in the dynamic culture system. The SFC scaffolds prepared through the directional lyophilization process showed radially aligned porous structures with increased swelling ratio and porosity, ameliorative mechanical stiffness that resembled the normal liver matrix more closely, and improved biocompatibility. The iHepLPCs displayed a hepatic plate-like distribution and differentiated into matured hepatocytes with improved hepatic function in vitro and in vivo. Moreover, hepatocyte–endothelial cell interphase arrangement was generated in the co-culture compartment with improved polarity, bile capillary formation, and enhanced liver functions compared with the monocultures. Thus, a more biomimetic hepatic lobule-like model was established and could provide a valuable and robust platform for various applications, including bioartificial liver and drug screening.